(untitled) (Bangabandhu Sheikh Mujib Medical University Journal, 2016)
Carcinoma of the lung is a malignant lung tumor characterized by uncontrolled cell growth in tissues of the lung. If left untreated, this growth can spread beyond the lung by process of metastasis into nearby tissue or other parts of the body. Various surgical modalities have been used with the treatment of lung cancer with variable results. We report a case of 80 years- old male admitted to National Institute of Chest Diseases and Hospital with dry cough for one month and chest pain for twenty days. On his physical examination there was no significant abnormality. Hematological and biochemical findings were also normal. In his CXR -P/A view showed a rounded opacity in the right lung field. It was diagnosed as a case of Squamous Cell Carcinoma of the right upper lobe of lung by a CT guided FNAC. We had performed segmentectomy of the lesion on right upper lobe by a right sided thoracotomy. Histopathological report confirmed the diagnosis and showed that the excised margins were free of tumor invasion. Patients recovery was uneventful. Patient was discharged on 15th post operative day with advice for further follow up and also referred to Oncology Department for further management. In conclusion this was a case of carcinoma lung which was successfully managed by surgical intervention due to judicious suspicion adequate evaluation and measures in time.